Ethos through traditional construction processes: Historical development between community builder in the Minho Area of the North-western Iberian Peninsula and Pico Island in the Azores. (March 2021) - Alcindor, Mónica; Lima, Ana; Alcindor-Huelva, Patricia
Abstract: This article analyses the developmental transitions in traditional construction processes in two very different but historically related contexts: the Island of Pico in the Azores and the Minho Area in the North-western Iberian Peninsula. The Pico Island, with a young geology, presents a serious limitation of available material resources, and resulting in a markedly individualistic approach to building. The Iberian Peninsula, on the other hand, with an abundance of material resources, presents a strongly collective approach to the organization of building works. This paper described the forms of organization necessary to achieve similar constructive systems, with the objective of making different material realities visible in the ethos of both. Activity-theoretical studies put an emphasis on the object enabling a longitudinal and rich analysis through time. A specific contribution in outlining the historical transformation of work of the community builder is made by using the life stories of two builders, one in Pico and another in the Minho Area, serving as the guiding thread. The paper shows that activity theory provides useful analytical tools for the enrichment of studies in constructive systems.